Strategi Keterampilan Membaca dalam Tujuan Instruksional Khusus Kelas 3 di Sekolah Dasar Negeri Buaran Jati 2 Kecamatan Sukadiri - Magdalena, Ina; Ramadanti, Saskia; Siregar, Epriliani Rahmita (Lembaga Yasin AlSys, 2021)
Reading must not be only an exciting activity, but also meaningful to one’s self-development in cognitive and affective aspect, including the language skill. In a formal education context in classrooms, reading needs specific methods or techniques in order to help students making meaning from their reading. This article is a literature study that analyzes reading strategies from various research results and journals, aiming to give information and arouse thinking for educators. It is hoped this writing makes inspirations for teachers to make innovations that requires literacy skill. The reading strategies are done before reading, while reading, and after reading. The pre-reading activities are building prior knowledge, predicting through visual text from the book cover, and questioning. The while-reading activities are making connection, visualizing, inferring, questioning, predicting, and self-monitoring. The post-reading activities are predicting, questioning, summarizing, and synthesizing. By applying those strategies, students develop their roles as good readers, which are as a decoder, meaning maker, text user, and text critic.